Optimized sound absorption of a rigid polyurethane foam - M. A. Ibrahim; R. W. Melik (Archives of Acoustics)
In this study, cast panel received as sound insulator was implemented as sound absorber. The panel is composed of prepainted metal skins with a rigid self extinguishing polyurethane foam. For the achievement of such material as sound absorber, holes are uniformly drilled in the sample to allow relatively easy access of sound to the interior structure. Using the two microphone impedance measurement tube, the sound absorption coefficient was studied for samples of different, coverings, opening pores (2 mm, 3 mm), open areas (0.04, 0.16), and at air space depths: 0, 5, 10, 20 and 40 mm from the reflected wall. The normalized acoustic impedance was also studied. The results revealed that when the sample was uniformly drilled with pores of opening 2~mm each to have 0.16 mm open area, and positioned at air space depth (5 mm), it showed optimum sound absorption greater than 0.80 in the frequency range from 700-1600 Hz. In dealing with noise reduction, this absorption gives, 6.9 dB drop in noise level.